Calcium and available phosphorus levels for laying hens in second production cycle - Pelicia,K (2009)
This experiment studied the effect of four calcium (3.0, 3.5, 4.0, and 4.5%) and four available phosphorus levels (0.25, 0.30, 0.35, and 0.40%) in the diet of semi-heavy commercial layers after molting. Hisex Brown® layers between 90 and 108 weeks of age were distributed in a completely randomized experimental design with a 4x4 factorial arrangement with 16 treatments of five replicates of eight birds each. mortality, egg production, feed intake, egg mass, average egg weight, calcium and phosphorus intake, feed conversion ratio (per dozen eggs and per kg eggs), eggshell percentage and thickness, eggshell strength, eggshell weight per surface area (ESWSA), yolk percentage and color, albumen percentage, albumen and yolk heights, and blood and excreta calcium and phosphorus concentrations. There was no interaction (P>0.05) between dietary Ca and avP for any of the studied parameters. There were linear increases in Ca intake (P<0.01), eggshell percentage (P<0.05); ESWSA (P<0.05); yolk color (P<0.05); Ca concentration in the blood (P<0.05) and excreta (P<0.01) as dietary Ca level increased. The intake of avP linearly increased (P<0.01) with dietary avP levels. The remaining parameters were not influenced (P>0.05) by dietary Ca and avP levels. The diet containing 4.5% calcium improved feed conversion ratio per dozen eggs and eggshell quality. The lowest avP level fed (0.25%) is sufficient to maintain the performance and the egg quality of semi-heavy commercial layers after molting.